The planet on our plates: approaches to incorporate environmental sustainability within food-based dietary guidelines - Dooren, Corné van; Loken, Brent; Lang, Tim; Meltzer, Helle Margrete; Halevy, Sarah; Neven, Loes; Rubens, Kristof; Seves-Santman, Marije; Trolle, Ellen (Frontiers in Nutrition, 2024)
The incorporation of environmental sustainability in food-based dietary guidelines (FBDGs) is an emerging field of study. Over the last decade, several countries have taken important steps to include the concept of environmental sustainability in guidelines that were previously reserved for advice on health. Past studies have mainly focused on the content of FBDGs in relation to environmental sustainability -the 'what'. This paper is the first to focus on the various approaches used by countries to incorporate environmental sustainability in FBDGs -the 'how' -and to assess the potential impact of these various approaches in achieving health and environmental goals. Given the potential of FBDGs as a policy tool for influencing food consumption, it is critical that we continually assess the current state of FBDGs, celebrate countries that have adopted ambitious FBDGs and push for increased ambition where necessary.